1990
DOI: 10.1159/000216113
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Platelet Activation in Type I Diabetics with Chronic Complications under Long-Term Near-Normoglycemic Control

Abstract: A prethrombotic state with altered, hyperactive platelets may contribute to the development of diabetic late complications. Whether increased platelet ‘in vivo’ activation can be reduced by tight metabolic control is controversial. We studied plasma markers of platelet activation in 64 long-term, microangiopathic type I diabetics after at least 18 months of intensive treatment for near-normoglycemia. Both platelet factor 4 and β-thromboglobulin proved to be significantly (p ≤ 0.05) elevated in comparison with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
1
11
0
1
Order By: Relevance
“…The HbA 1c levels indicate that the patients were in good long‐term glycemic control. The present data are in accordance with previous findings [14,31] that platelet and leukocyte hyperactivity takes place in Type 1 DM patients even under good metabolic control. Thus, platelet and leukocyte reactivity did not appear to be related to glycemic control among our DM patients.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The HbA 1c levels indicate that the patients were in good long‐term glycemic control. The present data are in accordance with previous findings [14,31] that platelet and leukocyte hyperactivity takes place in Type 1 DM patients even under good metabolic control. Thus, platelet and leukocyte reactivity did not appear to be related to glycemic control among our DM patients.…”
Section: Discussionsupporting
confidence: 94%
“…However, little is known about platelet–leukocyte cross‐talk in DM. It has been reported that diabetic microangiopathy is associated with increased platelet [13,14] and leukocyte [15] activation and increased heterotypic aggregation [11,16]. Thus, we compared platelet and leukocyte activation and platelet–leukocyte interactions among Type 1 DM patients without and with microangiopathy, and age‐ and gender‐matched healthy subjects, to clarify if there is enhanced platelet–leukocyte cross‐talk, and if this may contribute to platelet and leukocyte hyperreactivity in Type 1 DM.…”
Section: Introductionmentioning
confidence: 99%
“…39 Thus, hyperglycemia alone potentially accounts for at least part of the altered platelet response in patients with diabetes mellitus. This hypothesis is consistent with the observation that patients with type 1 diabetes mellitus have an increased risk of cardiovascular disease without concomitant dysipidemia and hypertension.…”
Section: Aspirin Resistancementioning
confidence: 99%
“…Leukozyten von Patienten mit Diabetes mellitus, vor allem Neutrophile, weisen abnorme Strukturen und eine erhöhte Chemotaxis auf. Diabetische Mikroangiopathie ist assoziiert mit erhöhter Aktivierung von Thrombozyten und Leukozyten sowie einer verstärkten Bildung von Thrombozyten-LeukozytenAggregaten [10,28,29].…”
Section: Gesteigerte Gerinnungsneigung Bei Diabetes Mellitusunclassified